Traumatic Brain Injury: Integrated Approach - Oliveira, Edson (2012)
Traumatic brain injury is a public health problem with significant economic and social impact. Its incidence has increased worldwide at the expense of developing countries and remains as the major cause of morbidity and mortality among young adults. The authors present a general and integrated approach of this pathology contextualizing epidemiological, pathophysiological, clinical and therapeutical aspects.